Multidimensional analysis of city images and basic information of respondents in multi-areal scale of mega city - Shouni Tang; Huizhen Yang; Wei Liu; Hongbo Qiao; Guoqing He; Linbing Lyu; Jun Wang (Journal of Asian Architecture and Building Engineering, 2023)
With the rapid development of urbanization, Wuhan has gradually developed into a mega city, and the city image has also changed. The main purpose of this study is to explore the differences in different dimensions of respondents’ attitudes towards city image in different areas of Wuhan and analyze the relationship between respondents’ basic information and attitude evaluation. Explore the development status of mega city image to better understand the feelings of urban users and guide the development direction of mega city image in the future. We used the questionnaire method to collect the basic information of the respondents and the evaluation data of the city image in the three dimensions and used SPSS to carry out descriptive statistics, correlation analysis and ANOVA analysis on the data. Through analysis of the data, we can get that different basic information of the respondents leads to different attitudes towards city images. Basic information of respondents is significantly correlated with the attitude towards city images. The differences between the rational planned new town with industrial production as its function and other areas are the largest in liking degree and familiarity degree, but there is no significant difference in the attitude of importance degree.